The association of patient characteristics and surgical variables on symptoms of pain and function over 5 years following primary hip-replacement surgery: a prospective cohort study - Judge, A; Arden, N; Batra, R; Thomas, G; Beard, D; Javaid, M; Cooper, C; Murray, D (BMJ Publishing Group, 2013)
OBJECTIVES: To identify patient characteristics and surgical factors associated with patient-reported outcomes over 5 years following primary total hip replacement (THR). DESIGN: Prospective cohort study. SETTING: Seven hospitals across England and Scotland. PARTICIPANTS: 1431 primary hip replacements for osteoarthritis. MAIN OUTCOME MEASURES: The Oxford Hip Score (OHS) was collected preoperatively and each year up to 5 years postoperatively. Repeated measures such as linear regression modelling are used to identify patient and surgical predictors of outcome and describe trends over time. RESULTS: The majority of patients demonstrated substantial improvement in pain/function in the first year after surgery-between 1 and 5 years follow-up, there was neither further improvement nor decline. The strongest determinant of attained postoperative OHS was the preoperative OHS-those with worse preoperative pain/function had worse postoperative pain/function. Other predictors with small but significant effects included: femoral component offset-women with an offset of 44 or more had better outcomes; age-compared to those aged 50-60, younger (age <50) and older patients (age >60) had worse outcome, increasing body mass index (BMI), more coexisting diseases and worse Short Form 36 mental health (MH) was related to worse postoperative pain/function. Assessment of change in OHS between preoperative  and postoperative assessments revealed that patients achieved substantial and clinically relevant symptomatic improvement (change), regardless of variation in these patient and surgical factors. CONCLUSIONS: Patients received substantial benefit from surgery, regardless of their preoperative assessments and surgical characteristics (baseline pain/function, age, BMI, comorbidities, MH and femoral component offset). Further research is needed to identify other factors that can improve our ability to identify patients at risk of poor outcomes from THR surgery.